Nuclear trafficking of the anti‐apoptotic Coxiella burnetii effector protein AnkG requires binding to p32 and Importin‐α1. (15th July 2016) - Schäfer, Walter; Eckart, Rita A.; Schmid, Benedikt; Cagköylü, Hasret; Hof, Kerstin; Muller, Yves A.; Amin, Bushra; Lührmann, Anja
Summary: The obligate intracellular bacterium Coxiella burnetii causes the zoonotic disease Q‐fever. Coxiella pathogenesis depends on a functional type IV secretion system (T4SS). The T4SS effector AnkG inhibits pathogen‐induced host cell apoptosis, which is believed to be important for the establishment of a persistent infection. However, the mode of action of AnkG is not fully understood. We have previously demonstrated that binding of AnkG to p32 is crucial for migration of AnkG into the nucleus and that nuclear localization of AnkG is essential for its anti‐apoptotic activity. Here, we compared the activity of AnkG from the C. burnetii strains Nine Mile and Dugway. Although there is only a single amino acid exchange at residue 11, we observed a difference in anti‐apoptotic activity and nuclear migration. Mutation of amino acid 11 to glutamic acid, threonine or valine results in AnkG mutants that had lost the anti‐apoptotic activity and the ability to migrate into the nucleus. We identified Importin‐α1 to bind to AnkG, but not to the mutants and concluded that binding of AnkG to p32 and Importin‐α1 is essential for migration into the nucleus. Also during Coxiella infection binding of AnkG to p32 and Importin‐α1 is crucial for nuclear localization of AnkG. Abstract : The obligate intracellular pathogen Coxiella burnetii uses a type IV secretion system (T4SS) to inhibit host cell death. Here we demonstrate that during C. burnetii infection the anti‐apoptotic T4SS effector AnkG is injected into the host cell, where it accumulates within the nucleus. Importantly, the nuclear localization of AnkG is essential for its anti‐apoptotic activity. The localization of AnkG and, thus, its activity is regulated by intracellular trafficking, which is controlled by the host cell proteins p32 and Importinα1